Latin America : the missing financial crisis - Porzecanski, Arturo C. (United Nations New YorkUS, 2009)
Reviews the progress made by many governments in Latin America in the past decade to reduce currency mismatches, allow for more flexible exchange-rate regimes, enhance the capitalisation, funding and supervision of their banking sytems, encourage the development of local capital markets, and implement sounder and more credible monetary and fiscal policies.